2005
DOI: 10.1128/aem.71.7.4121-4126.2005
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Microbial Gene Transcripts in Environmental Samples

Abstract: We analyzed gene expression in marine and freshwater bacterioplankton communities by the direct retrieval and analysis of microbial transcripts. Environmental mRNA, obtained from total RNA by subtractive hybridization of rRNA, was reverse transcribed, amplified with random primers, and cloned. Approximately 400 clones were analyzed, of which ϳ80% were unambiguously mRNA derived. mRNAs appeared to be from diverse taxonomic groups, including both Bacteria (mainly ␣-and ␥-Proteobacteria) and Archaea (mainly Eurya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
138
0
5

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 210 publications
(148 citation statements)
references
References 17 publications
(14 reference statements)
5
138
0
5
Order By: Relevance
“…The function of transposases in open ocean cyanobacteria is unknown, however in other related diazotrophic cyanobacteria, tranposases are present in high genome copy number and recently have been observed as dominant transcripts in situ (Hewson et al, 2009). The large number of conserved hypothetical proteins or proteins of unknown function (31 in the day and eight at night) is consistent with observations in other metatranscriptomic surveys (Poretsky et al, 2005(Poretsky et al, , 2009bFrias-Lopez et al, 2008;Gilbert et al, 2008;McGrath et al, 2008), and shows a need for prioritized studies of gene function.…”
Section: Transcript Library Gene Orthologssupporting
confidence: 64%
See 2 more Smart Citations
“…The function of transposases in open ocean cyanobacteria is unknown, however in other related diazotrophic cyanobacteria, tranposases are present in high genome copy number and recently have been observed as dominant transcripts in situ (Hewson et al, 2009). The large number of conserved hypothetical proteins or proteins of unknown function (31 in the day and eight at night) is consistent with observations in other metatranscriptomic surveys (Poretsky et al, 2005(Poretsky et al, , 2009bFrias-Lopez et al, 2008;Gilbert et al, 2008;McGrath et al, 2008), and shows a need for prioritized studies of gene function.…”
Section: Transcript Library Gene Orthologssupporting
confidence: 64%
“…Unlike metagenomic surveys which elucidate potential genetic capabilities (Tyson et al, 2004;Venter et al, 2004;Rusch et al, 2007), and which are mostly focused on the discovery of novel metabolic pathways or extent of diversity, metatranscriptomics provide information on active processes in dominant microorganisms (Poretsky et al, 2005(Poretsky et al, , 2009bFrias-Lopez et al, 2008). Metatranscriptomic studies to date have elucidated that a large proportion of genes expressed in open ocean assemblages have no known function, or show less similarity to cultivated microorganisms than metagenomic surveys (Frias-Lopez et al, 2008;Gilbert et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metatranscriptomics, the sequencing of messenger RNA (mRNA, representing expressed genes) from the environment, provides an unbiased view of the functionality of a microbial community as it is not constrained to targeting a specific phylogenetic group or metabolic pathway (Poretsky et al, 2005). To this point, metatranscriptomic analyses have shown community expression patterns over diel cycles or under enhanced CO 2 concentrations, as well as identified taxon-specific metabolic processes (Frias-Lopez et al, 2008;Gilbert et al, 2008;Hewson et al, 2009;Poretsky et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Recent applications of metatranscriptomics revealed differences in community gene expression in response to tidal and diel cycles (Frias-Lopez et al, 2008;Poretsky et al, 2005;Poretsky et al, in press) and in response to elevated CO 2 concentrations (Gilbert et al, 2008). These studies revealed a large component of sequences that are of unknown origin (that is, no hits to gene databases), including possibly intergenic spacer-encoded riboswitches and termination factors (Frias-Lopez et al, 2008;Gilbert et al, 2008;Poretsky et al, 2005;Poretsky et al, in press). Because sequencing is random, most sequences obtained in metagenomic and metatranscriptomic studies are from abundant taxa, and rarer organisms, such as C. watsonii, may be absent altogether (Johnston et al, 2005).…”
Section: Introductionmentioning
confidence: 99%